IMPLEMENTATION OF EPANET TECHNOLOGY IN THE DESIGN OF A CLEAN WATER SYSTEM IN DAMARKASIAN VILLAGE - Faqih, Nasyiin; Herlambang, Sigit; Sulistyowati, Yuli; Roehman, Fatchur; Mushthofa, Mushthofa (Universitas Islam Nahdlatul Ulama Jepara, 2025)
Water is a fundamental necessity that must be utilized wisely. This study was conducted in Damarkasian Village, located at the foot of Mount Sindoro and characterized by its hilly terrain. The village has a very limited supply of clean water, forcing residents to rely on a neighboring village for their water needs. Although there is a water distribution system in place, only wealthier residents can afford to build their own networks, while those less fortunate must rely on public facilities along the roadside. To address the uneven water distribution, a well-planned clean water distribution system based on gravity flow is essential. Field data collected includes spring water discharge, water quality, distance, and elevation, as well as population data from official statistics. Water discharge was measured using the volumetric method, and elevation and distance were recorded using the Q-GIS application. Network evaluation, conducted using EPANET 2.0 software, indicated a water discharge rate of 12.2 liters per second. To meet the village's water needs through 2037, a discharge rate of 10.57 liters per second is required. A total of 39 service tanks and appropriately sized PVC pipes are planned without the need for pumps, reducing costs. The total budget is estimated at IDR 1.4 billion, with a tariff of IDR 1,300/m³, cheaper than the PDAM rate.PENERAPAN TEKNOLOGI EPANET DALAM RANCANGAN SISTEM AIR BERSIH DI DESA DAMARKASIANAir adalah kebutuhan mendasar yang harus dimanfaatkan secara bijak. Penelitian ini dilakukan di Desa Damarkasian, yang terletak di kaki Gunung Sindoro dan memiliki kontur perbukitan. Sumber air bersih di desa ini sangat terbatas, sehingga penduduk bergantung pada desa tetangga untuk pasokan air. Meskipun ada distribusi air, hanya masyarakat yang mampu yang dapat membangun jaringan sendiri, sementara warga kurang mampu menggunakan fasilitas umum di pinggir jalan. Untuk mengatasi masalah distribusi air yang belum merata, diperlukan perencanaan sistem distribusi air bersih dengan sistem gravitasi. Data lapangan yang dikumpulkan mencakup debit mata air, kualitas air, jarak, dan elevasi, serta data penduduk dari badan statistik. Debit air diukur dengan metode volumetrik, dan elevasi serta jarak dengan aplikasi Q-GIS. Evaluasi jaringan menggunakan software EPANET 2.0 menunjukkan debit air sebesar 12,2 lt/detik. Untuk memenuhi kebutuhan penduduk hingga 2037, diperlukan debit 10,57 lt/detik. Sebanyak 39 bak pelayanan dan pipa PVC dengan diameter yang sesuai direncanakan tanpa pompa, yang menghemat biaya. Total anggaran sebesar Rp. 1,4 miliar, dengan tarif Rp. 1.300/m3, lebih murah dari PDAM.